Diagnostic utility of lung ultrasound in predicting the need for surfactant therapy in preterm neonates with respiratory distress - Singh, Pari; Patnaik, Suprabha; Verma, Arjun; Garegrat, Reema; Maheshwari, Rajesh; Suryawanshi, Pradeep (Frontiers in Pediatrics, 2023)
Background Lung ultrasound is an accurate and early predictor for surfactant replacement therapy in respiratory distress syndrome (RDS) as compared to clinical parameters and chest x-ray. However, lung pathologies for respiratory distress at birth have overlapping symptomatology and low middle-income countries have a higher incidence of congenital pneumonia, in addition to RDS, making the immediate diagnosis difficult. Thus, there is a need for assessing a cutoff for lung ultrasound scores in the given setting. Objectives The primary objective was to determine the diagnostic accuracy of the lung ultrasound score (LUS) in predicting the need for surfactant therapy in preterm neonates with respiratory distress. Secondary objectives were to correlate LUS with corresponding oxygen saturation to the fraction of inspired oxygen ratio (SpO2/FiO2), arterial/Alveolar oxygen pressure ratio (a/A), and chest x-ray (CXR) findings. Methodology A prospective observational study was carried out at a tertiary-level neonatal intensive care unit in India in 2022 enrolling 100 neonates <34 weeks gestational age with respiratory distress at birth. After initial stabilization of the neonate, LUS was performed and baseline parameters were noted. Surfactant was administered as per the 2019 European Consensus guidelines and LUS was repeated after 6 h of therapy. Results The mean gestation of enrolled neonates was 31.06 ± 2.12 weeks and the mean birthweight was 1,412 ± 391 g. Approximately 58% were diagnosed with RDS and 30% had congenital pneumonia. Surfactant was administered to 40% of neonates. The cutoff LUS for surfactant therapy was 7 [area under the curve (AUC) 0.977; 95% CI, 0.947–1; P < 0.001; with sensitivity 92.5%, specificity 96.67%, PPV 94.87%, and NPV 95.08%] and the cutoff LUS for the second dose of surfactant was 10 (AUC 0.964; 95% CI, 0.913–1; P < 0.001). The score decreased by 3.24 (2.44–4.05) after 6 h of the first dose and correlated significantly with SpO2/FiO2 ratio (−0.750), a/A ratio (−0.650), and CXR findings (0.801). Conclusion The study predicted an optimal LUS cutoff of 7 and 10 for the need for the first dose of surfactant and re-treatment, respectively, in neonates <34 weeks gestational age with respiratory distress.